Strong heterologous electron sink outcompetes alternative electron transport pathways in photosynthesis - Hubáček, Michal; Wey, Laura T.; Kourist, Robert; Malihan-Yap, Lenny; Nikkanen, Lauri; Allahverdiyeva, Yagut (John-Wiley & Sons, 2026)
Improvement of photosynthesis requires a thorough understanding of electron partitioning under both natural and strong electron sink conditions. We applied a wide array of state-of-the-art biophysical and biochemical techniques to thoroughly investigate the fate of photosynthetic electrons in the engineered cyanobacterium Synechocystis sp. PCC 6803, a blueprint for photosynthetic biotechnology, expressing the heterologous gene for ene-reductase, YqjM. This recombinant enzyme catalyses the reduction of an exogenously added substrate into the desired product by utilising photosynthetically produced NAD(P)H, enabling whole-cell biotransformation. Through coupling the biotransformation reaction with biophysical measurements, we demonstrated that the strong artificial electron sink, outcompetes the natural electron valves, the flavodiiron protein-driven Mehler-like reaction and cyclic electron transport. These results show that ferredoxin-NAD(P)H-oxidoreductase is the preferred route for delivering photosynthetic electrons from reduced ferredoxin and the cellular NADPH/NADP+ ratio as a key factor in orchestrating photosynthetic electron flux. These insights are crucial for understanding molecular mechanisms of photosynthetic electron transport and harnessing photosynthesis for sustainable bioproduction by engineering the cellular source/sink balance. Furthermore, we conclude that identifying the bioenergetic bottleneck of a heterologous electron sink is a crucial prerequisite for targeted engineering of photosynthetic biotransformation platforms.